Pressure Pain Threshold Values Obtained Through Algometers - Trueba, Jose Humberto; Gasparini, Francesca; Flores Cuautle, José de Jesús Agustín (Revista Mexicana de Ingenieria Biomedica, 2021)
A review of the scientific literature on pressure pain obtained through algometers is carried out. A comparison of the pain pressure thresholds (PPT) obtained or considered within the analyzed studies was performed. The primary outcome of this work is the collection of these PPT values concerning the body regions where the algometers applied the pressure: trapezius muscles, back muscles, upper extremities, leg muscles, foot area, and muscles of the head. Furthermore, a comparison between the results of manual and electromechanical algometers is presented. Several tables are created, which can be useful to compare future studies that adopt pressure algometers. These values can also be considered a reference to evaluate the accuracy and reliability of new algometers, either manual or electromechanical. Besides, from the information obtained, the design requirements of an electromechanical pressure algometer are presented. These requirements are defined to develop a portable instrument that is also smaller, lighter, and cheaper than the existing ones and can measure the pressure in different parts of the human body.